Catalytically engineered reduced graphene oxide/ZnO hybrid nanocomposites for the adsorption, photoactivity and selective oil pick-up from aqueous media1. Issue 62 (8th July 2015) - Babitha, K. B.; Jani Matilda, J.; Peer Mohamed, A.; Ananthakumar, S.
<x xml:space="preserve">Abstract</x> Microwave mediated in situ growth of nanocrystalline ZnO on rGO nanosheets is achieved using APTMS as the crosslinking agent. The deposition of hydrophobic ZnO/Si@rGO on a simple cotton textile results in the selective adsorption of oil from aqueous media.